Metabolic and Fatigue Profiles Are Comparable Between Prepubertal Children and Well-Trained Adult Endurance Athletes - Birat, Anthony; Bourdier, Pierre; Piponnier, Enzo; Blazevich, Anthony J.; Maciejewski, Hugo; Duché, Pascale; Ratel, Sébastien (Frontiers in Physiology, 2018)
The aim of this study was to determine whether prepubertal children are metabolically comparable to well-trained adult endurance athletes and if this translates into similar fatigue rates during high-intensity exercise in both populations. On two different occasions, 12 prepubertal boys (10.5 ± 1.1 y), 12 untrained men (21.2 ± 1.5 y) and 13 endurance male athletes (21.5 ± 2.7 y) completed an incremental test to determine the power output at VO2max (PVO2max) and a Wingate test to evaluate the maximal anaerobic power (Pmax) and relative decrement in power output (i.e. the fatigue index, FI). Furthermore, oxygen uptake (VO2), heart rate (HR) and capillary blood lactate concentration ([La]) were measured to determine (i) the net aerobic contribution at 5-s intervals during the Wingate test, and (ii) the post-exercise recovery kinetics of VO2, HR and [La]. The Pmax-to-PVO2max ratio was not significantly different between children (1.9 ± 0.5) and endurance athletes (2.1 ± 0.2) but lower than untrained men (3.2 ± 0.3, p < 0.001 for both). The relative energy contribution derived from oxidative metabolism was also similar in children and endurance athletes but greater than untrained men over the second half of the Wingate test (p < 0.001 for both). Furthermore, the post-exercise recovery kinetics of VO2, HR and [La] in children and endurance athletes were faster than those of untrained men. Finally, FI was comparable between children and endurance athletes (-35.2 ± 9.6 vs. -41.8 ± 9.4%, respectively) but lower than untrained men (-51.8 ± 4.1%, p < 0.01). To conclude, prepubertal children were observed to be metabolically comparable to well-trained adult endurance athletes, and were thus less fatigable during high-intensity exercise than untrained adults.